Concurrent sexual partnerships among female sex workers and their non-commercial male partners in Tijuana and Ciudad Juárez, Mexico. Issue 4 (20th November 2012) - Robertson, Angela Marie; Syvertsen, Jennifer L; Rangel, M Gudelia; Staines, Hugo S; Morris, Martina; Patterson, Thomas L; Ulibarri, Monica D; Strathdee, Steffanie A
Abstract : Objectives: To investigate the prevalence and correlates of concurrent (overlapping) sexual partnerships among female sex workers (FSWs) and their non-commercial male partners in two Mexico–US border cities. Methods: A cross-sectional survey of FSWs and their non-commercial male partners was conducted in Tijuana and Ciudad Juárez, Mexico (2010–2011). Eligible FSWs and verified non-commercial partners were aged ≥18 years; FSWs had ever used hard drugs (lifetime) and recently exchanged sex for money, drugs or other goods (past month). Participants underwent baseline questionnaires obtaining dates of sex and condom use with ≤5 other recurring partners, including FSWs' regular clients. These dates were compared with dates of sex with enrolled study partners to determine overlap (ie, 'recurring' concurrency). Bivariate probit regression identified recurring concurrency correlates. Results: Among 428 individuals (214 couples), past-year recurring concurrency prevalence was 16% and was higher among women than their non-commercial male partners (26% vs 6%). In 10 couples (5%), both partners reported recurring concurrency. The majority of couples (64%) always had unprotected sex, and most of the individuals (70%) with recurring concurrency 'sometimes' or 'never' used condoms with their concurrent partners. Recurring concurrency was positively associated with FSWs' income, men's caballerismo (a form of traditional masculinity) and men's belief that their FSW partners had sexually transmitted infections (STIs). Conclusions: Recurring concurrency, representing sustained periods of overlapping partnerships in which unprotected sex was common, should be addressed by couple-based STI prevention interventions.